Audience Perception of Broadcast Media Coverage of the Effect of the Covid-19 Pandemic on Women in Rural Communities in Edo State, Nigeria - ROSEMARY, Ikeme; CHUKWU, Obinna Johnkennedy (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose: This study examines audience perception of broadcast media coverage of the effect of the COVID-19 pandemic on women in rural communities in Edo State. The researcher embarked on this study with the intent of achieving three objectives, and based on the objectives of the study, three research questions were formulated to serve as a guide for this study.Methodology: The study is anchored on the attitude change theory, and data was collected through the secondary data collection method. Findings show that Women in rural areas have been disproportionately affected by the pandemic, as they often face unique challenges such as limited access to healthcare, education, and economic opportunities.Findings:These challenges have been exacerbated by COVID-19 and the measures implemented to contain its spread, such as lockdowns and travel restrictions. This study recommends that broadcast media coverage of the effects of COVID-19 on women in rural communities should focus on human stories that resonate with the audience.Implication:It can be achieved by featuring real-life women from rural communities affected by the pandemic. The media can showcase how COVID-19 has impacted these women, their challenges, and how they cope. By highlighting individual stories, the media can make the issue more relatable to the audience, which will help to increase engagement and understanding.